Highly biocompatible jujube polysaccharide-stabilized palladium nanoparticles with excellent catalytic performance. (1st May 2019) - Guo, Xiaolei; Zhang, Jin; Cui, Yanshuai; Chen, Shengfu; Sun, Haotian; Yang, Qinghua; Ma, Guanglong; Wang, Longgang; Kang, Jianxin
Abstract : Jujube polysaccharide-stabilized palladium nanoparticles provide active sites for efficient catalysis of 4-nitrophenol to 4-aminophenol. Abstract : The development of stable and biocompatible palladium nanoparticles (Pd NPs) catalysts has been drawing great interest. In this study, Pd NPs were prepared through a green method, where jujube polysaccharide (JP) was employed as both reducing and stabilizing agents for the first time. The JP stabilized palladium nanoparticles (Pd n -JP NPs) displayed small size, high stability, good biocompatibility and excellent catalytic efficiency. Pd50 -JP NPs showed high stability up to two weeks in solutions of a wide pH range (4–9). Pd50 -JP NPs showed negligible cytotoxicity against HeLa cells at a high concentration of up to 400 μg mL −1 . Furthermore, Pd n -JP NPs showed excellent catalytic activity for reduction of 4-nitrophenol (4-NP) in the presence of sodium borohydride (NaBH4 ). The normalized rate constant ( k nor ) and turnover frequency (TOF) of Pd50 -JP NPs were as high as 38.4 s −1 mM −1 and 4455 h −1, respectively. The prepared Pd n -JP NPs will have various potential applications in bio-related catalysis in the future.